2016
DOI: 10.1166/jnn.2016.12339
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of LaF3:Eu3+ Based Inorganic–Organic Hybrid Nanostructures via an Ion Exchange Method and Their Strong Luminescence

Abstract: Lanthanide doped inorganic-organic hybrid nanostructures have received much attention in recent years due to their strong luminescence sensitized by organic ligands via an energy transfer route. In this work, an ion exchange method was used to prepare Eu3+ doped LaF3 based inorganic-organic hybrid nanostructures with organic ligands. The undoped LaF3 nanoparticles were first synthesized by a hydrothermal method, and Eu3+ ions were then ion exchanged into these LaF. nanoparticles to form the Eu3+ doped LaF3 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The absorption peak at 742 cm −1 was attributed to the out‐of‐plane bending vibration of the benzene ring. [ 11 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The absorption peak at 742 cm −1 was attributed to the out‐of‐plane bending vibration of the benzene ring. [ 11 ]…”
Section: Resultsmentioning
confidence: 99%
“…The AR value of LaF 3 :5%Eu 3+ prepared by the hydrothermal method was 27.63% that of the LaF 3 :5%Eu 3+ prepared by Wang X.J. [ 11 ] This indicated that the lattice distortion of LaF 3 :Eu 3+ prepared by the hydrothermal method was less than that of LaF 3 :Eu 3+ prepared by the ion‐exchange method under the same Eu 3+ doping concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the emission peaks excited by an exciting light at 397 nm are the characteristic emissions of Eu 3+ ions, and they are assigned to the high-energy transition 5 D 2 → 7 F 3 at 515 nm and 5 D 1 → 7 F J (J = 0–2) at 530 nm, 541 nm, and 561 nm; low-energy transition 5 D 0 → 7 F J (J = 1–4) at 598 nm, 622 nm, 657 nm, and 702 nm, respectively [8,35]. The weaker emission peak at 598 nm corresponding to 5 D 0 → 7 F 1 is allowed by the magnetic dipole transitions due to Eu 3+ ions, located at a site with inversion symmetry, while the stronger emission peak at 622 nm, corresponding to 5 D 0 → 7 F 2 , is allowed by the electric dipole transitions that are a result of absence of inversion symmetry at the Eu 3+ lattice site [36,37,38,39].…”
Section: Resultsmentioning
confidence: 99%